Synthesis and In Vitro Evaluation of Bis‐intercalators with Varied Linkers between Aminochloropyrimidine Rings. (17th March 2014) - Zhao, Y.; McCarthy, P. J.; Párkányi, C.
<x xml:space="preserve">Abstract</x> The synthesis of two groups of aminochloropyrimidine bis‐intercalators with different lipophilicity or limited flexibility of linkers as potential DNA intercalators is described. The lipophilic linkers in the synthesized bis‐intercalators are represented by alternating methylene groups and oxygen atoms in a chain, with a pyrimidine ring containing an amino group and a chloro group at each end (10, 11, 12, 13). The bis‐intercalators with limited flexibility contain chains with two benzene rings (15, 16, 17, 18, 19). All these compounds were obtained by nucleophilic substitution of 2‐amino‐4, 6‐dichloropyrimidine (1). The spectral data and other physical properties of the new compounds are presented. The anticancer activity of these newly synthesized compounds is also reported. Compounds 7 and 8 described in one of our previous publications display good anticancer activity against murine lymphoma.